The World's First Feminist Foreign Policy: Four Years Later - Sörbom,Hannah (2019)
In 2014 Sweden declared itself the first country in the world to launch a feminist foreign policy. It was four years ago and Sweden is now preparing for a new government, hence this thesis aims to evaluate what feminist foreign policy has meant for Sweden's 2014-2018 government. To answer the research question an evaluation of the government controlled agencies SIDA and the Armed forces together with Sweden's Foreign Minister Margot Wallström speeches held during this time and her twitter account has been conducted. The analysis indicates actions has been made to carry out the feminist foreign policy aims. The conclusion that can be drawn is that the Swedish government has been ambitious in its interests of conducting intersectional feminist foreign policy but besides from that not much information or practical considerations can be found showing how the feminist foreign policy is much different from previous foreign policy.
Keywords: Feminist foreign policy; Evaluation; Margot Wallström; SIDA; Armed Forces